Does the Degree of Campus "Wiredness" Matter? - Hu, Shouping; Kuh, George D. (Education Policy Analysis Archives, 2001)
Responses to the College Student Experience Questionnaire 4th Edition from 18,844 students at 71 colleges and universities were analyzed to determine if the presence of computing and information technology influenced the frequency of use of various forms of technology and other educational resources and the exposure to good educational practices. Undergraduates attending "more wired" campuses as determined by the 1998 and 1999 Yahoo! Most Wired Campus survey more frequently used computing and information technology and reported higher levels of engagement in good educational practices than their counterparts at less wired institutions. Non-traditional students benefited less than traditional students, but both women and men students benefited comparably from campus "wiredness."